A scoping review on the influence of safety culture and safety communication on safety performance among employees at construction sites in the Middle East - Abdul Wahat, Nor Wahiza; Suleiman, Nurul Nasukha (Human Resources Management Academic Research Society (HRMARS), 2024)
The study strives to investigate the influence of safety culture and safety communication on safety performance among construction site employees in the Middle East through utilisation of scoping review and theme analysis. The objective of this scoping review is to thoroughly analyse and combine the current body of literature by applying certain criteria to include or exclude relevant sources. A comprehensive search was performed on various primary indexing databases, including Scopus and Google Scholar, as well as several other journal databases such as ProQuest, STARS, and ScienceDirect. The search technique utilised a mixture of keywords pertaining to safety culture, safety communication, safety performance, construction, and associated terminology. The inclusion criteria consisted of peer-reviewed articles and thesis studies that specifically examined the impact of safety culture and communication on safety performance in construction sites located in the Middle East. This scoping review is conducted in two separate cycles to gather scoping results from two distinct variable relationships: safety culture and safety performance, as well as safety communication and safety performance.